An Islamic Economic Review of The Pay Later Culture and Consumptive Lifestyle - Rahmah, Avivi Kayla Bikratuna; Isman, Isman (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to: a) analyze Islamic economic law regarding transaction mechanisms and penalties in paylater services in Indonesia based on the principles of the DSN-MUI fatwa. b) describe the influence of paylater culture on consumptive lifestyle behavior from an Islamic economic perspective. Methodology: This research is qualitative in nature and descriptive-analytical in scope. The technique used is documentation study or literature study. Results: 1) The Islamic economic law review of transaction mechanisms and penalties in paylater services in Indonesia based on the principles of the DSN-MUI fatwa is as follows: paylater services are permitted as long as they do not conflict with sharia principles, namely avoiding elements of usury, gharar (uncertainty), maysir (gambling), tadlis (deception), dharar (harm), and zhulm (injustice). And in order for the paylater system to be in accordance with sharia, the services must use valid contracts, including: Murabahah or Bay' Bithaman Ajil, Qardh, Ijarah, Wakalah bi al-Ujrah. 2) The influence of paylater culture on consumptive lifestyle behavior from an Islamic economic perspective causes Muslims to fall into: a) Israf (extravagance) b) Tabdzir, c) Neglect of Priority Scale Applications/Originality/Value: With the convenience of this pay later service feature, many Muslims, especially young people, have become complacent and less attentive to how religion regulates it. Therefore, this topic needs to be reviewed in order to add to the Sharia literature.